Fatherhood arrested : parenting from within the juvenile justice system - Nurse, Anne, 1968- (Vanderbilt University Press, 2002)
Studies the effects that jail time and parole have on the relationships between young fathers and their children, with research revealing how the prison structure and its programs help fathers stay in touch with sons and daughters.